Lipids, pH, and Their Interaction Affect the Inhibitory Effects of Carvacrol against Salmonella Typhimurium PT4 and Escherichia coli O157:H7 - Carvalho, Rhayane I.; de Jesus Medeiros, Andrea S.; Chaves, Maísa; de Souza, Evandro L.; Magnani, Marciane (Frontiers in Microbiology, 2018)
Although carvacrol (CAR) is considered an alternative antimicrobial for use in food, few is known about the influence of food-related parameters on its inhibitory effects against pathogens. This study assessed the influence of different amounts of proteins, using beef extract (BE) as a protein-rich source, lipids (LIP), using sunflower oil as a LIP-rich source, and pH values or their interaction on the inhibitory effects of CAR against Salmonella Typhimurium PT4 (ST) and Escherichia coli O157:H7 (EC). The specific maximum growth rate (μmax) and lag phase duration (λ) of the test pathogens when exposed to CAR in media with different amounts of BE (4, 6 and 8 g/100 mL), LIP (3.75, 5 and 6.25 mL/100 mL) and pH values (5, 5.5 and 6) were determined. The viable counts of the tested pathogens in media that promoted the highest and lowest μmax in the presence of CAR were monitored during 24 h. The lowest μmax of ST and EC exposed to 2.4 μL/mL (-1.29 and -0.82 log CFU/mL/h, respectively) or 4.8 μL/mL CAR (-1.44 and -2.17 log CFU/mL/h, respectively) were observed in media with the highest LIP amount (6.25 mL/100mL) and pH value (pH 6). For both SE and EC, the longest λ (> 2 h) was verified in media where these pathogens showed the lowest μmax. These data indicate that the concomitant increase in LIP amounts and pH values affected positively the CAR inhibitory effects against the target pathogens. CAR (2.4 or 4.8 μL/mL) failed to inhibit the increase in ST and EC counts in media where the highest μmax values were previously observed. On the contrary, CAR inhibited the increase of ST counts (final counts 5 log CFU/mL) and decreased the EC counts (final counts 3.5 log CFU/mL) in media where the lowest μmax values were observed. These results show that the inhibitory effects of CAR on ST and EC in food matrices could be affected as a function of the interaction of LIP amounts and pH values.